Activation of the Human Angiotensin-(1-12)-Chymase Pathway in Rats With Human Angiotensinogen Gene Transcripts - Ferrario, Carlos M.; VonCannon, Jessica; Ahmad, Sarfaraz; Wright, Kendra N.; Roberts, Drew J.; Wang, Hao; Yamashita, Tomohisa; Groban, Leanne; Cheng, Che Ping; Collawn, James F.; Dell'Italia, Louis J.; Varagic, Jasmina (Frontiers in Cardiovascular Medicine, 2019)
The recent discovery of angiotensin-(1-12) [Ang-(1-12)] as an alternate substrate for tissue angiotensin II (Ang II) formation underscores the potential importance of alternative renin-independent pathway(s) for the generation of active peptides from angiotensinogen. Since renin-angiotensinogen enzymatic activity is species-specific, a transgenic model of hypertension due to insertion of the human angiotensinogen gene in Sprague Dawley (SD) rats allowed for characterizing the contribution of a non-renin dependent mechanism for Ang II actions in the blood and heart tissue of rats expressing the human amino acid sequence of the angiotensinogen gene in their genome. Plasma and cardiac expression of angiotensins, plasma renin activity and cardiac enzymatic activities of chymase, angiotensin converting enzyme (ACE) and ACE2 were determined in TGR(hAGT)L1623 rats given vehicle or valsartan orally for 2 weeks. The antihypertensive effect of valsartan after 14-day treatment augmented plasma concentrations of angiotensin I (Ang I) and Ang II without significant changes in rat and human Ang-(1-12) levels. Blockade of Ang II AT1- receptors (AT1-R) produced a 46 % rise in left ventricular content of human Ang-(1-12) concentration and no changes in rat cardiac Ang-(1-12) levels. Failure of valsartan to alter cardiac content of human Ang-(1-12) levels was verified by Mass-Spectroscopy which also confirmed a greater than 4-fold increase in cardiac Ang II content in transgenic rats given vehicle and compared to rats SD control rats. Cardiac chymase and ACE2 activities, significantly higher than ACE activity in TGR(hAGT)L1623 rats, were not altered by blockade of AT1-R. The humanized model of angiotensinogen-dependent hypertension expresses the human sequence of Ang-(1-12) in plasma and cardiac tissue and responds to AT1-R blockade with further increases in the levels of the peptide in the heart tissue. Since rat renin has no hydrolytic activity on human angiotensinogen, the study stresses the importance of a renin-independent mechanism forming elevated levels of Ang II in the circulation as well as the heart.